2017
DOI: 10.1111/jvim.14839
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐blind, Placebo‐controlled, Multicenter, Prospective, Randomized Study of Beraprost Sodium Treatment for Cats with Chronic Kidney Disease

Abstract: BackgroundChronic kidney disease (CKD) is a common progressive and irreversible disease in cats. The efficacy and safety of beraprost sodium (BPS) in cats with CKD have not been evaluated.Hypothesis/ObjectivesTo evaluate the efficacy and safety of BPS in the treatment of cats with CKD, as compared to placebo.AnimalsSeventy‐four client‐owned cats with naturally occurring CKD.MethodsDouble‐blind, placebo‐controlled, multicenter, prospective, randomized trial. The cats received BPS (55 μg/cat) or a placebo PO q12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 36 publications
1
16
0
Order By: Relevance
“…In CKD cats, the mechanism of tubulointerstitial fibrosis is similar to that in humans, confirming its usefulness as a model of human CKD [ 13 ]. BPS significantly inhibited the increase in serum creatinine (SCr) levels in a randomized controlled trial in cats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In CKD cats, the mechanism of tubulointerstitial fibrosis is similar to that in humans, confirming its usefulness as a model of human CKD [ 13 ]. BPS significantly inhibited the increase in serum creatinine (SCr) levels in a randomized controlled trial in cats [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 Additionally, the renoprotective effect of BPS has also been shown in other animal models of CKD, which further explained the possible mechanism of BPS. 22,24,25 BPS improved renal function by inhibiting inflammatory factor expression, apoptosis in renal microvascular endothelial and tubular epithelial cells, and tubulointerstitial fibrosis. 26,27 Koyama et al.…”
Section: Discussionmentioning
confidence: 97%
“…The results of the current study showed that the multicomponent, multitarget combination SUC is noninferior to the commonly used ACEI benazepril for the treatment of cats with CKD of mild to moderate severity, with similar effects on laboratory parameters indicative of disease progression. Review of the current literature showed that most tested drugs are noninferior compared to benazepril [21][22][23][24][42][43][44][45] (Table 4). Some of the indicated studies included a placebo group to confirm effectivity of their study drug [22,23,42,45,46].…”
Section: Discussionmentioning
confidence: 99%
“…Review of the current literature showed that most tested drugs are noninferior compared to benazepril [21][22][23][24][42][43][44][45] (Table 4). Some of the indicated studies included a placebo group to confirm effectivity of their study drug [22,23,42,45,46]. Mizutani et al [22] and Takenaka et al [45] showed an increase in serum creatinine within the treatment time of 180 days in the placebo group, showing the progressive course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation